PEMBERDAYAAN KADER KESEHATAN DALAM PENINGKATAN PENGELUARAN ASI PADA IBU POSTPARTUM DENGAN TEHNIK MERMET - Lustiani, Ika; Sari, Dwinda; Fairuza, Filda (Jurnal Abdimas Bina Bangsa, 2024)
The proposed community service activities take the form of The cadres' role is crucial to enhancing the local community's quality of life and well-being, encouraging the implementation of development programs, and strengthening the community. Problems with growth and development are experienced by infants who do not receive exclusively breast milk. Banten Area gets restrictive breastfeeding, with the least rate in Serang City at 41.4%. There are numerous ways of expanding bosom milk creation, one of which is the Mermet technique. The Shapiro-Wilk statistical test is utilized in the one-group pretest-posttest design of this Community Service project, which makes use of the quantitative Quasy Experiment method. The examining method for this exploration was all out testing of 12 respondents. The examination time is May-June 2024. The consequences of this Abdimas show that the negative position when the factual test yield got a huge worth of 0.000, a critical aftereffect of 5% (p-esteem = 0.000 - 0.05). The conclusion is that it is accepted that the mermet technique in community services increases breast milk production in postpartum mothers